2010
DOI: 10.1007/s12272-010-0203-8
|View full text |Cite
|
Sign up to set email alerts
|

Two new c-glucosyl benzoic acids and flavonoids from Mallotus nanus and their antioxidant activity

Abstract: Two new 2-C-β-D-glucopyranosyl benzoic acid derivatives named mallonanosides A (1) and B (2) were isolated from the methanolic extract of the leaves of Mallotus nanus along with five known flavonoids, kaempferin (3), juglanin (4), quercitrin (5), myricitrin (6), and rhoifolin (7). Their structures were established on the basis of spectral and chemical evidence. Their antioxidant activities were shown to depend on the number of hydroxyl groups, and the location and species of sugar moiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…On the basis of 1-D, 2-D NMR and UV-Vis spectral analyses, their structures were elucidated as 1,4-dihydroxy-3,4-(epoxyethano)-5-cyclohexene (1) (Hase et al 1995) and cleroindicin E (2) (Tian et al 1997) from the dichloromethane extract, lupeol (3) (Baek et al 2010), methyl p-coumarate (4) (Chaabi et al 2010) and methyl 4-hydroxybenzoate (5) (Owen C et al 2003) from the diethyl ether extract, prunin (6) (Turner et al 2005), 5,7,2ʹ,5ʹ-tetrahydroxyflavanone 7-glucoside (7) (Aquino et al 1990), protocatechuic acid (8) (Lee et al 2011), luteolin 7-glucoside (9) (Liu et al 2012) and apigenin (10) (Owen RW et al 2003) from the ethyl acetate extract; and naringin (11) Downloaded by [Cambridge University Library] at 10:24 11 August 2015 (Yoon et al 2012), rhoifolin (12) ) and luteolin 7-glucuronate (13) (Ringl et al 2007) from the n-butanol extract. Compounds 3, 4, 5, 8, 9, 10, 11 and 12 are known antioxidant agents (Van Kiem et al 2010;Moussouni et al 2011;Hugo et al 2012;Begum & Prasad 2012;Thangavel et al 2012;Santiago & Mayor 2014;Song & Park 2014;Hlila et al 2015) and may be responsible for the significant exhibited antioxidant capacity of the diethyl ether, ethyl acetate and n-butanol extracts of the plant. The compounds 3, 10 and 11 have already proved their antidiabetic potential by inhibiting the aldose reductase enzyme (Goodarzi et al 2006;Jung et al 2011;Ramu et al 2014) and may be responsible for the potent pharmacological activity and therapeutic role of T. humilis against the long-term diabetic complications and specifically the diethyl ether, ethyl acetate and n-butanol extracts of the plant.…”
Section: Structural Elucidation Of the Isolated Compoundsmentioning
confidence: 99%
“…On the basis of 1-D, 2-D NMR and UV-Vis spectral analyses, their structures were elucidated as 1,4-dihydroxy-3,4-(epoxyethano)-5-cyclohexene (1) (Hase et al 1995) and cleroindicin E (2) (Tian et al 1997) from the dichloromethane extract, lupeol (3) (Baek et al 2010), methyl p-coumarate (4) (Chaabi et al 2010) and methyl 4-hydroxybenzoate (5) (Owen C et al 2003) from the diethyl ether extract, prunin (6) (Turner et al 2005), 5,7,2ʹ,5ʹ-tetrahydroxyflavanone 7-glucoside (7) (Aquino et al 1990), protocatechuic acid (8) (Lee et al 2011), luteolin 7-glucoside (9) (Liu et al 2012) and apigenin (10) (Owen RW et al 2003) from the ethyl acetate extract; and naringin (11) Downloaded by [Cambridge University Library] at 10:24 11 August 2015 (Yoon et al 2012), rhoifolin (12) ) and luteolin 7-glucuronate (13) (Ringl et al 2007) from the n-butanol extract. Compounds 3, 4, 5, 8, 9, 10, 11 and 12 are known antioxidant agents (Van Kiem et al 2010;Moussouni et al 2011;Hugo et al 2012;Begum & Prasad 2012;Thangavel et al 2012;Santiago & Mayor 2014;Song & Park 2014;Hlila et al 2015) and may be responsible for the significant exhibited antioxidant capacity of the diethyl ether, ethyl acetate and n-butanol extracts of the plant. The compounds 3, 10 and 11 have already proved their antidiabetic potential by inhibiting the aldose reductase enzyme (Goodarzi et al 2006;Jung et al 2011;Ramu et al 2014) and may be responsible for the potent pharmacological activity and therapeutic role of T. humilis against the long-term diabetic complications and specifically the diethyl ether, ethyl acetate and n-butanol extracts of the plant.…”
Section: Structural Elucidation Of the Isolated Compoundsmentioning
confidence: 99%
“…In recent years, an increasing number of studies have been carried out on the role of flavonoids in the prevention and treatment of bone diseases. For example, kaempferol, genistein, quercetin, and naringin have been proven to be capable of protecting bones by inhibiting osteoclastic differentiation and function (Forte et al, ; Kim et al, ; Phan et al, ; X. C. Wang et al, ; T. Xu et al, ). Rhoifolin, one of the main flavonoids derived from either Turpinia arguta or Exocarpium Citri grandis, has been shown to display antioxidant and blood pressure‐decreasing effects (Phan et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that plant-derived compounds possess potential anti-mutagenic, anti-inflammatory and anticarcinogenic properties, and are gaining considerable attention regarding the prevention and inhibition of UVB-induced skin damage ( 32 ). Juglanin is a natural compound extracted from crude Polygonum aviculare , which exhibits inhibitory activity against inflammation and cancer growth ( 7 ). In the present study, juglanin was topically applied to UVB-exposed SKH-1 hairless mice by gavage in order to explore its effects on inflammatory markers, and the p38/JNK and PI3K/AKT-associated apoptosis signaling pathways ( 33 ).…”
Section: Discussionmentioning
confidence: 99%